Five acres of forestry - Hendershot, William A. (My University, 1904)
Introduction: The average Kansas farmer is too busy to plant a few acres of forest trees. If he would stop a few minutes and figure, and look a few decades into the future and see the results, he would greatly improve his farm, and if all the farmers would have a few acres of forest, the farms of Kansas would rapidly increase in value. A farm of 160 A should have about 5 A. of forest, and larger farms proportionate. This is the minimum limit a farmer should raise. What benefit is a forest to the farmer? 1 It can be used for a wind break. 2 It furnishes posts and wood. 3 It enriches the soil. 4 It produces ties and timber. 5 It catches dirt driven by storms. 6 It checks winds, and land from washing. 7 It adds beauty to the country. It is a good plan, if one is going to raise a forest, to plant it for a double purpose. First to raise a few acres of trees. Second to secure a wind break or prevent a slouch from washing. Some farmers allow their stock to ramble among their forest trees. This is a poor plan as the cattle will destroy the tender shoots, and trample the ground so that it becomes hard and the water will run off instead of soaking into the ground. Trees require a vast amount of water and therefore none should be wasted. The trees are ruined if when young, the tops are broken out. This makes crooked trees.
Citation: Hendershot, William A. Five acres of forestry. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Forestry; Trees; Farmers; Agriculture; Agricultural Techniques; Theses